Leveraging logistic models to enhance nutrient dynamics modeling in intercropped spring wheat with varied nitrogen and phosphorus fertilization strategies. - Yue Feng; Ying Ma; Renqiang Deng; Bo Wang; Haiyan Tian; Xin Liu; Qi Dong; Aiping Wang; Sumera Anwar (PLoS ONE)
Intercropping systems offer substantial benefits in crop yield nd nutrient absorption. Utilizing logistic models, we simulated the dynamic of nutrient uptake and accumulation in spring wheat and the impact of different planting patterns and compound fertilizer application rates on spring wheat yield. We conducted a field experiment involving two planting patterns: spring wheat monoculture (MS) and spring wheat-pea intercropping (MI), with five compound fertilizer applications: C0 (0 kg ha-1), C1 (480 kg ha-1), C2 (540 kg ha-1), C3 (600 kg ha-1), and C4 (660 kg ha-1). We assessed spring wheat yield and aboveground nitrogen (N) and phosphorus (P) accumulation under different planting patterns and fertilization treatments. Results revealed that intercropping significantly increased spike number, grains per spike, and grain yield of spring wheat by 3.7%, 6.3%, and 13.3%, respectively, compared to monoculture. Fertilization treatments notably enhanced average spring wheat grain yield, with C2 performing optimally. Logistic model analysis indicated that under intercropping, the maximum accumulated aboveground N and N uptake rate (v) of spring wheat was 11.4% and 13.2% higher, and the maximum accumulated P and maximum P uptake rate (Vmax) were 11.3% and 9.5% higher, respectively, compared to monoculture. Intercropped spring wheat under C2 exhibited the highest P accumulation among all treatments. In conclusion, both intercropping and fertilization can enhance N and P uptake and accumulation in spring wheat, thereby boosting yield. Optimized yield can be achieved under C2 (540 kg h-1) with a 10% reduction in fertilizer application. Thus effective control of fertilizer application is pivotal for maximizing the yield advantage of the spring wheat/pea intercropping system.